Intrinsic Motivation and Institutional Limitations: Key Implementation Determinants of Psychological First Aid Training - Rojas-Andrade, R (Springer, 2024)
Psychological first aid (PFA) trainings are conducted to train frontline care workers in practical and emotional support to people who have been recently affected by stressful events. The aim of this study was to describe the determinants of the implementation behavior of a PFA training strategy in Chile and to provide theoretical information on the factors that influence trainers’ self-efficacy. For this purpose, the Determinants of Implementation Behavior Questionnaire, administered online to a sample of 117 PFA trainers throughout Chile, was used. The results indicate that the main facilitators for implementation originate in the intrinsic motivation of the trainers, while the barriers are mainly found in the limited institutional opportunities offered by the context. Evidence was also found on the effect of motivation and context on trainer self-efficacy. PFA trainers may need to invest a lot of psychological resources to overcome the barriers encountered during implementation. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.